High-molecular-weight esters in α-pinene ozonolysis secondary organic aerosol: structural characterization and mechanistic proposal for their formation from highly oxygenated molecules - A. Kahnt; A. Kahnt; R. Vermeylen; R. Vermeylen; Y. Iinuma; Y. Iinuma; M. Safi Shalamzari; M. Safi Shalamzari; W. Maenhaut; M. Claeys (Atmospheric Chemistry and Physics, 2018)
Stable high-molecular-weight esters are present in α-pinene ozonolysis secondary organic aerosol (SOA) with the two most abundant ones corresponding to a hydroxypinonyl ester of cis-pinic acid with a molecular weight (MW) of 368 (C19H28O7) and a diaterpenylic ester of cis-pinic acid with a MW of 358 (C17H26O8). However, their molecular structures are not completely elucidated and their relationship with highly oxygenated molecules (HOMs) in the gas phase is still unclear. In this study, liquid chromatography in combination with positive ion electrospray ionization mass spectrometry has been performed on high-molecular-weight esters present in α-pinene ozonolysis SOA with and without derivatization into methyl esters. Unambiguous evidence could be obtained for the molecular structure of the MW 368 ester in that it corresponds to an ester of cis-pinic acid where the carboxyl substituent of the dimethylcyclobutane ring and not the methylcarboxyl substituent is esterified with 7-hydroxypinonic acid. The same linkage was already proposed in previous work for the MW 358 ester (Yasmeen et al., 2010), but could be supported in the present study. Guided by the molecular structures of these stable esters, we propose a formation mechanism from gas-phase HOMs that takes into account the formation of an unstable C19H28O11 product, which is detected as a major species in α-pinene ozonolysis experiments as well as in the pristine forest atmosphere by chemical ionization–atmospheric pressure ionization–time-of-flight mass spectrometry with nitrate clustering (Ehn et al., 2012, 2014). It is suggested that an acyl peroxy radical related to cis-pinic acid (RO2⚫) and an alkoxy radical related to 7- or 5-hydroxypinonic acid (R′O⚫) serve as key gas-phase radicals and combine according to a RO2 + R′O⚫  →  RO3R′ radical termination reaction. Subsequently, the unstable C19H28O11 HOM species decompose through the loss of oxygen or ketene from the inner part containing a labile trioxide function and the conversion of the unstable acyl hydroperoxide groups to carboxyl groups, resulting in stable esters with a molecular composition of C19H28O7 (MW 368) and C17H26O8 (MW 358), respectively. The proposed mechanism is supported by several observations reported in the literature. On the basis of the indirect evidence presented in this study, we hypothesize that RO2 + R′O⚫  →  RO3R′ chemistry is at the underlying molecular basis of high-molecular-weight ester formation upon α-pinene ozonolysis and may thus be of importance for new particle formation and growth in pristine forested environments.